Translations of Famous Masterpiece “Boburnoma” Into the World Languages - Kazakova Ra’no Mashrabayevna (International Journal on Integrated Education, 2022)
this article tells about the translations of masterpiece "Boburnoma" into different languages such as English, Russian…, conducted scientific research and the first publications in English and in Russian.